Analisis Kebutuhan Desain Model Pembelajaran Komunitas Sosial untuk Meningkatkan Keterampilan Menulis Teks Eksposisi di SMK - Ai Santi; Khaerudin Kurniawan; Yunus Abidin (Universitas Mulawarman, 2023)
Writing learning is a process aimed at developing students' creativity in writing. One of the writing lessons taught at school is writing expository texts. Expository texts are texts that contain explanations of information and knowledge. In learning to write, teachers should guide and facilitate students with good, appropriate, and quality teaching to achieve optimal learning objectives. In line with this, this study aims to find out the initial analysis in the form of a set of information needed for the learning model development program. The learning model developed is a social community learning model in learning exposition writing at Vocational High School (SMK). The research method used is descriptive qualitative conducted by survey method. Based on the research findings and data analysis, teachers need a new learning model to support learning effectiveness and students achieve learning objectives. Students learn in groups and prefer learning with peer tutors during the learning process. Learning that involves friends has been known that students can understand the material, solve problems together, and improve their skills.